Avaliação de deslocamentos em vigas de concreto com armaduras de aço e de polímeros reforçados por fibras - Melo, Laila Monteiro Alves (2019)
Although, in general, the serviceability limit states – such as excessive deflections, visible cracks and excessive vibration – do not bring direct loss to the safety of the structures they can cause discomfort and mistrust to the users and must be projected and, when it is possible, minimized in structural projects. Corrosion of steel reinforcement in aggressive environments can cause considerable damage in reinforced concrete structures. Fiber reinforced polymer (FRP) bars have emerged as an alternative to steel for elements subjected to those environments. The mechanical properties of FRP bars can yield to large crack widths and deflections. As a result, the design of concrete elements reinforced with FRP materials is often governed by the serviceability limit states. The analysis of deflections can be done in different levels of sophistication, from non-linear analysis to the use of simplified equations that seek to represent an equivalent stiffness of the cracked beam, such as the equations that are prescribed in codes related to design of reinforced concrete structures for the calculation of displacements. This work investigates practical procedures proposed in norms and published works for the investigation of displacements in concrete beams reinforced with steel and fiber reinforced polymer. The displacements calculated using such procedures are compared to values obtained experimentally, found in the literature. The partial results obtained indicate that the studied models present more satisfactory results in elements with high reinforcement ratio. The evaluation of the displacements was done through a code developed on the Matlab® platform.